Flow in commercial experiences : A study in the subjective dynamics of the flow state, personal characteristics and customer satisfaction - Huhtamaa, Lauri (fi=Turun yliopisto|en=University of Turku|, 2018)
In the recent decades, the focus on the details of customer experience has been shifting from purely functional and utilitarian values towards more emotional and hedonistic approach. No longer the services are seen as something to be get done in the most conventional way possible, but as something that evokes feelings and gets customers immersed into. This is what commercial experiences are about. Consequently, marketing research in this field is shifting towards subjective sensations and personal preferences over the more universal concept of value gained. But to succeed in this transition and to really gain insight what happens in commercial experiences, input from another field of science is required. Considering that the commercial experiences are co-created with the customer, relatively small amount of psychological research has been utilized while studying it. In this thesis this will be addressed by reviewing a vast amount of literature considering the flow state. It is a subjective state of mind in which the individual loses the self-reflective thoughts and track of time while being extremely focused to the task at hand and thus capable of performing actions without consciously thinking of executing those. Flow should often emerge in the well-designed commercial experiences and is particularly interesting from the marketing standpoint, since it is intrinsically rewarding. It feels good to be in flow. Deriving from the theory concerning flow, there are many subjective factors affecting the intensity and prevalence if it. To explore the functionality of these individual nuances in marketing research, the objective of this study was set to understand the dynamics behind personal characteristics, experienced flow state and customer satisfaction. The personal characteristics chosen based on the relevance to the flow state were stress, motivation and personality. To unveil the connections between these multiple concepts close to the flow state, a quantitative research utilizing a partial least squares (PLS) structural equation modelling method was conducted with data gathered by surveying customers visiting in a commercial experience. The analysis revealed that the intensity of the flow state notably contributes to the customer satisfaction. Stress and personality affected the intensity of flow, which again was discovered to appear in two distinct phenomena, fluency of experience and immersion. Many of the measured concepts interacted together, but only immersion, losing the self-reflective thoughts and track of time, had a direct link to satisfaction. Interestingly, the intensity the customers experienced flow also had a connection to the frequency they visit commercial experiences. To summarize, this study illustrates the crucial role of the flow state in the creation of a commercial experience.